2005
DOI: 10.1097/01.blo.0000176150.16509.33
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructed Patellar Tendon Length after Proximal Tibia Prosthetic Replacement

Abstract: A common problem after proximal tibia prosthetic reconstruction is insufficient extensor mechanism or extensor lag. Maintaining the reconstructed patellar tendon length is an important way to minimize extensor lag. We measured the patellar tendon length and extensor lag serially. From 1994-2003, seven consecutive patients with malignant bone tumors of the proximal tibia had prosthetic reconstruction. The extensor mechanism was reconstructed by reattachment of the patellar tendon to the prosthesis with a synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 16 publications
2
27
0
3
Order By: Relevance
“…2 and 4). Shimose et al [37], in a case-series of seven patients, also observed that the patellar tendon stretched during the first few months postoperatively by about the same amount as found in our series. In contrast to our results, the extensor lag improved continuously in that series.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…2 and 4). Shimose et al [37], in a case-series of seven patients, also observed that the patellar tendon stretched during the first few months postoperatively by about the same amount as found in our series. In contrast to our results, the extensor lag improved continuously in that series.…”
Section: Discussionsupporting
confidence: 89%
“…2) [37]. The Blackburne-Peel Index describes the relationship of the patella to the trochlea by relating the length of the articular surface of the patella to the distance of the inferior patella to the tibial plateau.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations